Yield of magnetic resonance cholangiopancreatography for the investigation of bile duct dilatation in asymptomatic patients. Issue 3 (1st April 2017) - Tamir, Shlomit; Braun, Marius; Issachar, Assaf; Bachar, Gil N; Benjaminov, Ofer
Abstract : Background: Biliary dilatation in the asymptomatic patient is a frequent incidental finding in the work‐up for which there are no current guidelines. Objectives: The purpose of this study was to determine the yield of magnetic resonance cholangiopancreatography (MRCP) in asymptomatic patients with an incidental finding of biliary duct dilatation. Methods: The study included 68 consecutive patients for evaluation of biliary duct dilatation found incidentally on computed tomography (CT) or ultrasound (US). MRCP scans were reviewed, and data were retrospectively collected on demographics and laboratory work‐up. Patients were divided by the presence of a significant or non‐significant MRCP findings explaining the biliary duct dilatation and compared for normal or abnormal liver function. Results: Liver function was normal in 47 patients and abnormal in 21 patients. MRCP identified the cause of the bile duct dilatation in 41 patients (60.3%). Rates of insignificant causes were 51% in the normal‐liver‐function group and 7% in the abnormal‐function group. Corresponding rates of significant causes were 27.7% and 61.9% ( p = 0.007). Conclusions: MRCP is a valuable tool in the work‐up of biliary duct dilatation. Although significantly more significant causes of bile dilatation are identified in patients with abnormal liver function, almost one‐third of patients with normal liver function need further work‐up. This has important implications for establishing criteria for the use of MRCP in asymptomatic patients with biliary dilatation.